Glutamic acid decarboxylase antibody-spectrum disorders and type 1 diabetes mellitus in a patient following allogenic hematopoietic cell transplantation with review of literature - Shinichiro Sano; Taemi Ogura; Takayuki Takachi; Yuki Murai; Yasuko Fujisawa; Tsutomu Ogata; Kenichiro Watanabe; Masaki Yoshimura (Endocrine Journal)
Glutamic acid decarboxylase (GAD) is an enzyme that catalyzes the conversion of glutamic acid into γ-aminobutyric acid (GABA), the primary inhibitory neurotransmitter in the central nervous system (CNS). GAD is widely expressed in the CNS and pancreatic β-cells. GABA produced by GAD plays a role in regulating insulin secretion in pancreatic islets. Anti-GAD antibody is an established marker of type 1 diabetes mellitus (T1DM) and is also associated with stiff-person syndrome (SPS) and several other neurological disorders, including ataxia, cognitive impairment, limbic encephalitis, and epilepsy, collectively referred to as GAD antibody-spectrum disorders (GAD-SD). We report the case of a 17-year-old male patient who developed GAD-SD and T1DM after allogeneic hematopoietic cell transplantation (HCT). He presented with memory disorders, including feelings of déjà vu, accompanied by vomiting and headaches, and exhibited abnormal brain magnetic resonance imaging and electroencephalogram results. In addition to elevated fasting plasma glucose and glycated hemoglobin levels, markedly elevated anti-GAD antibody levels were detected in the serum and cerebrospinal fluid. Based on these findings, the patient was diagnosed with GAD-SD and T1DM and treated with methylprednisolone, followed by multiple daily insulin injections. We also reviewed previously reported cases of GAD-SD following HCT and multiple positive islet-related antibodies.